Penerapan Flipdeep Melalui Project Based Learning pada Membaca Nyaring Siswa Kelas IV: Penelitian - Latifah; Ridha Yogie Wardhani; Elisa Setia Putri; Zaki Hilmi Alhawariyin; Panca Dewi Purwati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the implementation of the Flipdeep learning material and to analyze its improvement on fourth–grade students’ oral reading skills of new vocabulary at SDN Gajah 2. Flipdeep was developed as a flipbook–based digital learning medium integrated with the Project Based Learning approach, enabling students not only to read texts but also to engage in simple project activities that strengthen vocabulary understanding and pronunciation. This research employed a descriptive method using observation, oral reading assessments, and teacher interviews as data collection techniques. The findings indicate that Flipdeep effectively improved students’ oral reading skills, as shown by the enhancement of pronunciation, intonation, and fluency. Visual representation, pronunciation models, and gradual reading exercises in Flipdeep supported students in comprehending new vocabulary more easily. In addition, students demonstrated increased motivation, confidence, and participation through project activities that encouraged collaboration and communication. The teacher viewed Flipdeep as feasible and practical due to its simple display, clear structure, and alignment with the Merdeka Curriculum principles. Therefore, Flipdeep is recommended as an innovative learning material to improve elementary school students’ oral reading abilities.